PHONOTACTICS OF AUTISTIC CHILDREN IN LAGOS STATE, NIGERIA (2023)
Phonotactics, which accounts for sound patterning, is affected by language regression in children with autism. Existing linguistic studies on autism in Nigeria focused mainly on general description of the disorder and developmental challenges. However, little attention was devoted to systematic description of their phonological patterns. Therefore, this study was designed to examine the speech production of autistic children in Lagos State, Nigeria, with a view to describing the phonological processes involved in the production of phonemes and syllables and the constraint ranking responsible for them. Alan Prince and Paul Smolensky’s Optimality Theory served as the framework, while the descriptive design was adopted. The convenience sampling technique was employed to select four special-needs facilities in three local government areas (Amuwo-odofin, Badagry, and Ikeja) of Lagos State. Availability of and accessibility to relevant data necessitated the selection of the facilities. Twenty-four children with autism under the age of 17 years (Amuwo-odofin: 17, Badagry: 2, and Ikeja: 5) accessing the facilities were purposively selected. Speeches of the participants were audio-recorded twice a week for two years. The data were subjected to phonological and acoustic analyses. Three phonological processes were dominant: deletion, substitution and epenthesis. Vowels were generally modified. Deletion was dominant in the rendition of consonants, with the lateral sound /l/ mostly affected. Substitution and epenthesis affected mainly vowels. Central vowels /ᴧ, ɜ, ə/ were strengthened and /ɔ/, /e/, /æ/ were used for each, respectively. Epenthesis was prominent in the realisation of vocalic phonemes, with /ɪ/ and /ə/ substituted as /i:/ and /æ/, respectively. It was also dominant in the articulation of triphthongs /eɪə/ and /ɔɪə/. Monophthongs were either retained or substituted with long or strong vowels. Diphthongs were monophthongised or substituted with stronger versions. Triphthongs were either substituted with diphthongs or epenthesised with an intrusive /j/, creating disyllabic sounds. With regard to syllables, simple onsets were produced comfortably more than complex onsets, while both simple and complex codas were deleted, reduced or produced with great difficulty. Constraint ranking favoured markedness over faithfulness. The constraints responsible for vowels were *SCHWA, NOCODA, NODIPH and *HIATUS. *COMPLEX ONSET and *COMPLEX CODA were the markedness constraints accountable for the simplified outcome of complex onsets, complex codas, open and closed syllables. *HIATUS was ranked above MAX-V for the emergence of minimum syllables. Consonant clusters, especially at coda positions, were reduced or rendered open, as *COMPLEX CODA was preferred above MAX. There were inconsistencies in the intensity values. The values were either abnormally high (73.94dB) or low (52. 89dB). Against a threshold of 63.42dB, their pitch values were either extremely high or low. The phonotactics of autistic children in Lagos State, Nigeria is characterised by simplification of difficult phonemes and syllables through deployment of deletion, substitution and epenthesis. Therefore, multidisciplinary therapists should be employed to improve the treatment and rehabilitation of autistic children.